2007
DOI: 10.1093/pasj/59.sp2.s515
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Camera (IRC) Deep Survey in the Performance-Verification Phase

Abstract: We report the first results of a near-and mid-infrared deep survey with the Infrared Camera (IRC) onboard AKARI in the performance verification phase. Simultaneous observations by the NIR, MIR-S and MIR-L channels of the IRC with effective integration times of 4529, 4908, and 4417 seconds at 3, 7, and 15 µm, covering 86.0, 70.3, and 77.3 arcmin 2 area, detected 955, 298 and 277 sources, respectively. The 5 σ detection limits of the survey are 6.0, 31.5 and 71.2µJy and the 50 % completeness limit are 24.0, 47.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 35 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…for the NIR bands and about 0.6 -0.8 mag for the MIR bands (except for L24 which has a relatively larger difference of 1.0 mag.) Wada et al (2007) also found a similar trend in the differences between the 5σ detection limits and 50% completeness limits for the NEP-Deep data. By comparing a single exposure and stacked image of ten exposures, they found that the 50% limits do not improve much for the NIR bands, while the improvements for the MIR bands are close to the square-root of the exposure time.…”
Section: Detection Limits and Completenesssupporting
confidence: 68%
See 1 more Smart Citation
“…for the NIR bands and about 0.6 -0.8 mag for the MIR bands (except for L24 which has a relatively larger difference of 1.0 mag.) Wada et al (2007) also found a similar trend in the differences between the 5σ detection limits and 50% completeness limits for the NEP-Deep data. By comparing a single exposure and stacked image of ten exposures, they found that the 50% limits do not improve much for the NIR bands, while the improvements for the MIR bands are close to the square-root of the exposure time.…”
Section: Detection Limits and Completenesssupporting
confidence: 68%
“…On the basis of these results, they concluded that the NIR bands are affected by the source confusion. In fact, the improvement in the 50% limit between one pointing and ten pointing observations is only a factor of 1.15 (Wada et al 2007) for the N3 band, implying that the source confusion could be significant.…”
Section: Detection Limits and Completenessmentioning
confidence: 99%
“…The earliest surveys were by the Infrared Space Observatory (ISO; Elbaz et al 1999;Gruppioni et al 2002;Rodighiero et al 2004) at 15 μm. Larger and deeper surveys came from Akari/IRC at 15 μm and the Spitzer/IRS peakup imager at 16 μm (Wada et al 2007;Burgarella et al 2009;Pearson et al 2010;Teplitz et al 2011). The present study uses photometric catalogs from the latter two surveys.…”
Section: The 16 μM Selected Samplementioning
confidence: 99%
“…We used the NEP deep survey data at two wavelength bands, 2.4 and 3.2 µm. Only a portion (∼30%) of the NEP deep survey area is selected to produce a reliable mosaicked image (the top panel of Figure 1) since some parts of the survey data are affected by the earthshine (Wada et al 2007) and a planetary nebula.…”
Section: Introductionmentioning
confidence: 99%